INFLUENCE OF GENDER DIFFERENCE IN THE ANTIDEPRESSANT EFFECT OF FLUOXETINE IN MICE IN TAIL SUSPENSION TEST - Anki; Walia, Vaibhav (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Aim: To determine the effect of gender difference in the antidepressant effect of fluoxetine (FLX) in mice in tail suspension test (TST). Methods: Swiss albino mice of either sex were used and the depression-like behavior was measured by TST. Results: The present study showed that there was a significant difference in the immobility period of male mice and female mice in TST. However, the antidepressant effect of FLX differs significantly in male mice and female mice in TST. Conclusion: It has been concluded that the antidepressant effect of FLX in TST was affected by the gender difference as suggested by the results of the present study. Keywords: Depression, Estrogen, Female, Fluoxetine, Mice, Serotonin.